Microstructure and texture analysis of δ‐hydride precipitation in Zircaloy‐4 materials by electron microscopy and neutron diffraction. (4th February 2014) - Wang, Zhiyang; Garbe, Ulf; Li, Huijun; Wang, Yanbo; Studer, Andrew J.; Sun, Guangai; Harrison, Robert P.; Liao, Xiaozhou; Vicente Alvarez, M. A.; Santisteban, J. R.; Kong, Charlie
<x xml:space="preserve">Abstract</x> This work presents a detailed microstructure and texture study of various hydrided Zircaloy‐4 materials by neutron diffraction and microscopy. The results show that the precipitated δ‐ZrH1.66 generally follows the δ(111)//α(0001) and δ[<inline-graphic xlink:href="ark:/27927/pgg4sp40zvf" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />]//α[<inline-graphic xlink:href="ark:/27927/pgg4sp40ztw" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />] orientation relationship with the α‐Zr matrix. The δ‐hydride displays a weak texture that is determined by the texture of the α‐Zr matrix, and this dependence essentially originates from the observed orientation correlation between α‐Zr and δ‐hydride. Neutron diffraction line profile analysis and high‐resolution transmission electron microscopy observations reveal a significant number of dislocations present in the δ‐hydride, with an estimated average density one order of magnitude higher than that in the α‐Zr matrix, which contributes to the accommodation of the substantial misfit strains associated with hydride precipitation in the α‐Zr matrix. The present observations provide an insight into the behaviour of δ‐hydride precipitation in zirconium alloys and may help with understanding the induced embrittling effect of hydrides.